Performance analysis in wheelchair para-badminton matches - Mota-Ribeiro, W.; Bezerra de Almeida, M. (International Journal of Racket Sports Science, 2020)
Para-badminton has performance classes which consider the impairment degree of each athlete; two of them use a wheelchair and are identified as Wheelchair 1 (WH1) and Wheelchair 2 (WH2). Due to the difference in functionality of players between the classes, the match characteristics of WH1 and WH2 games are expected to be different. Therefore, the objective of our study was to describe and compare the temporal and technical characteristics of classes WH1 and WH2. Twenty-three matches covering both WH1 and WH2 classes for men`s singles performed during the first phase of Brazil Para-badminton Championship 2018 were filmed and assessed. There were differences between all temporal characteristics, except in relation to the rally time and frequency of strokes, which suggested that the WH2 matches were more intense and more prolonged. Both clear and net-lift strokes were the techniques most used by the two classes. The WH2 class showed a higher frequency of total strokes, net-shot, smash, block and non-forced errors (p<0.05) than the WH21 class. Regarding the winning of points, the net-lift and service led to higher wins in WH1. Drop-shot and clear (WH1), and net-shot and dropshot (WH2) were the highest occurring shots leading to winning points.